Promoting Emotional Literacy and Character Values in Elementary Students: A Service-Learning Approach at Bunklotok School - Indah Larassari; Ana Hipzana; Eka Rahmadani; Neni Wardiani; Nurul Qur’ani; Baiq Novia Indah Kirana; Adam Baldawin; Agus Kurnia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Syarifuddin Lumajang, 2025)
The low quality of character education in elementary schools is reflected in the frequent occurrence of students’ non-empathic behaviors, such as bullying, using harsh words, and difficulties in managing their own emotions. This issue poses a challenge in creating a socially and emotionally healthy learning environment. The student community-service program carried out at SDN Bunklotok, Central Lombok, aimed to instill character values and emotional intelligence in students through educational and participatory approaches. The activities implemented the Service Learning (SL) method combined with the Participatory Action Research (PAR) approach, designed through interactive learning activities such as exercise sessions, ice breaking, games, inspirational stories, quizzes, and a “tree of hope,” supported by animated materials from Inside Out. The results show an improvement in students’ understanding of basic emotions and emotional management, as well as increased empathy and respect for others. Pretest and posttest activities indicated improvements in students' comprehension, and high enthusiasm was observed during quizzes and discussions. In conclusion, character education designed creatively and involving students' emotional engagement proves effective in shaping character awareness from the elementary level.